Naşterile în contexte diferite de cel marital - Hărăguș, Mihaela (Calitatea Vieții, 2011)
More than one quarter of all births registered annually in Romania are non-marital. We investigate this phenomenon, in our attempt to see whether this behaviour is post-modern or is an expression of socio-economic disadvantages. We conduct our analysis on Generations and Gender Survey (2005) data, whose retrospective design allows us to reconstruct the partnership and fertility histories of almost 6,000 women. Thus, we can approach the topic of non-marital childbearing from the life course perspective, by the technique of event history analysis. We will investigate the effect of different factors on the risk of childbearing in a context different than marriage: characteristics of parental home and the family environment where the woman grew up (urban/rural, residence with both parents, number of siblings, mother’s education), as well as the effect of personal characteristics (education level). We will differentiate and approach separately births of single mothers (those not being in a co-residential relationship at the moment of birth) and births in consensual unions, comparing them with marital births. Results show that childbearing outside marriage in Romania is rather associated with socio-economic disadvantages and a low level of education.